Thermal Potential of a Twin-Screw Compressor as Thermoelectric Energy Harvesting Source - Savescu, Claudia; Petrescu, Valentin; Comeaga, Daniel; Carlanescu, Razvan; Roman, Mihaela; Lale, Daniel; Mitru, Andrei (Engineering, Technology & Applied Science Research, 2024)
This study evaluates the potential of a twin-screw compressor as a heat source to harness thermal energy. Thermoelectric generators are a feasible solution for microenergy harvesting from waste heat based on the Seebeck effect. Thermographic infrared images of the compressor were used to assess potential installation spots. The physical mounting of the thermoelectric modules must consider certain hindering aspects. At first, the compressor skid is subject to standards and authorizations for its components, leaving only a couple of spots for screw-mounted module installations. Another inconvenience is the bonds in any thermoelectric material causing them not to withstand lateral mechanical stress in other directions except the c-axis perpendicular to the layers. Therefore, vibration measurements have to be performed beforehand. Numerical simulations were conducted, relying on the acquired thermoelectric modules as well as on the temperature and vibration data measured on the compressor. The thermoelectric generators studied are part of a multisource piezoelectric and thermoelectric energy harvesting system under research and development.